2018
DOI: 10.1051/bioconf/20181002036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extruder screws speed and process temperature on the extrudate shape changes of the maize-spelt blends

Abstract: Abstract. The objective of the study was examination of changes in the shape factors of extruded products, which occur as a result of different settings of the extrusion process variables. Samples analysed included products created by means of the extrusion process from a mixture of spelt flour and cornmeal, with the share of spelt at 70 to 100%. The samples were made with the use of a corotating twin screw extruder. Two speeds of extruder screw rotation (300 and 350 rpm) as well as two levels of temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…The extrudates obtained at 300-350 rpm screw speed had the best properties. Tomasz, Adam, Adam, and Jacek (2018) also reported that 300-350 rpm screw speed would produce an acceptable snack product from maize-spelt.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…The extrudates obtained at 300-350 rpm screw speed had the best properties. Tomasz, Adam, Adam, and Jacek (2018) also reported that 300-350 rpm screw speed would produce an acceptable snack product from maize-spelt.…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Selain itu, penurunan PD dan BD akibat peningkatan suhu juga dapat disebabkan karena pada suhu tinggi terjadi peningkatan superheating dari air yang mendukung pertumbuhan gelembung-gelembung udara dan meningkatkan volume ekstrudat (Singha et al, 2018). Tomasz et al, (2018) menyampaikan bahwa ukuran partikel bahan dan kecepatan screw ekstruder juga dapat mempengaruhi densitas ekstrudat. oleh rasio kacang merah, suhu ekstruder, maupun interaksi antar keduanya secara signifikan (p>0,05).…”
Section: Densitas Partikel (Pd) Dan Densitas Curah (Bd)unclassified